Efektivitas Penggunaan Bahasa Isyarat Manually Coded dalam Meningkatkan Komunikasi Anak Tunarungu Di SLB Dharma Bhakti Dharma Pertiwi Bandar Lampung - Yolanda, Evi; Maisuhetn, Maisuhetn; Utami, Ratna Tri (Universitas Pahlawan Tuanku Tambusai, 2025)
Children with hearing impairments (deafness) are individuals who experience loss of hearing ability, either partially or completely. This study aims to determine the effectiveness of the use of Sign Language for deaf children Manually Coded (BIM) in improving communication of deaf children at SLB Dharma Bakti Pertiwi Lampung. The research method used is descriptive quantitative with data collection techniques through observation, an experimental approach with a one-group pre-test, post-test design. The results of the study indicate that the consistent application of BIM in the learning process can improve the communication skills of deaf children, both in understanding the subject matter and in interacting socially in the school environment. After the study was conducted, the results obtained by students A and B experienced a significant increase of 20%. And the important effect of this learning process is that students feel safe and confident. Teachers who are trained in the use of BIM are able to facilitate a more inclusive and effective learning process. In addition, the use of BIM also increases the confidence and active participation of deaf students in learning activities. Thus, the use of BIM is proven to be effective as a communication and learning medium for deaf children at SLB Dharma Bakti Pertiwi Lampung. My suggestion is that simple training can help students develop optimal language skills. Future research could involve more subjects of various ages.